When factored it is: (3k+5)(k-1)
4 plus (4 squared) = 8
Take 3k from both sides to get k-3 equals 4, so k is 7
(j^3 + 3k^4)(j^6 - 3j^3k^4 + 9k^8)
If the equation has equal roots then the discriminant of b^2 -4ac = 0:- Equation: kx^2 +x^2 +kx +k +1 = 0 Discriminant: k^2 -4(k+1)(k+1) = 0 Multiplying out brackets: k^2 -4k^2 -8k -4 = 0 Collecting like terms: -3k^2 -8k -4 = 0 Divide all terms by -1: 3k^2 +8k +4 = 0 Factorizing: (3k +2)(k +2) = 0 => k = -2/3 or k = -2 Therefore possible values of k are -2/3 or -2
When factored it is: (3k+5)(k-1)
(3k - 2)(3k - 2) or (3k - 2)2
4 plus (4 squared) = 8
k=4
16 - 3k + 5 and k is 4, then 16 -12 + 5 = 9
Take 3k from both sides to get k-3 equals 4, so k is 7
285
Assuming the thing is as written and there are no brackets missed out then it is just 4 squared times 3 = 16x3=48.
1 squared plus 8 squared or 4 squared plus 7 squared
(j^3 + 3k^4)(j^6 - 3j^3k^4 + 9k^8)
4 squared plus 4 squared divided by 4 plus 4
9 plus 16=25 3 squared is the same as 3 times three and 4 squared is the same as 4 times 4 3 times 3 + 4 times 4 9 plus 16 = 25